Staff Responsiveness and Passenger Satisfaction in Tanzania’s Standard Gauge Railway Services - Mrisho, Tamimu; Massawe, Laurencia; Onesmo, Clashon (Journal of Industrial Engineering & Management Research, 2025)
This study examined the influence of staff responsiveness on passenger satisfaction in Tanzania’s Standard Gauge Railway (SGR) services. Staff responsiveness forms a critical component of service quality in transport operations, encompassing prompt assistance, courteous communication, and professional interaction between service providers and passengers. Using a mixed-methods approach, the study collected quantitative data from 117 passengers through structured questionnaires and qualitative data from key informant interviews. Quantitative results showed that respondents were generally satisfied with staff responsiveness, recording high mean scores for prompt response, courtesy, and assistance (mean values ranging between 3.81 and 4.13). However, regression analysis revealed that staff responsiveness had an insignificant statistical influence on overall passenger satisfaction (R² = 0.013; p > 0.05). Qualitative results complemented these findings, indicating that while passengers appreciated politeness and professionalism, responsiveness alone did not fully determine satisfaction due to communication challenges and limited staffing during peak hours. The study concludes that passenger satisfaction in SGR operations is multidimensional and depends on the integration of staff responsiveness with other service quality factors such as scheduling and facility standards. It recommends continuous staff training, improved communication systems, and coordinated service delivery to enhance passenger experience.